Isolamento e seleção de fungos filamentosos produtores de celulases a partir de resíduos agroindustriais. - Verônica de Souza Miranda Pacheco (2016)
Cellulases are the third largest industrial enzymes worldwide. These enzymes are applied in various industries such as textile, pulp and paper, juice extraction, detergents, animal feed and bioethanol production. Enzymes produced by microorganisms are preferred due to their biochemical diversity and ease of genetic manipulation. Filamentous fungi have shown their great potential for secreting enzymes. The present work aimed to isolate and select filamentous fungi from agroindustrial residues with potential cellulolytic activity. The filamentous fungi were isolated from the following agroindustrial residues: sugarcane bagasse, peanut shell and coconut shell, and selected in Petri dishes containing carboxymethylcellulose (CMC) agar according to their Enzymatic Index (EI). The obtainment of crude enzymatic preparation to quantify the total cellulolytic activity (FPase) occurred under submerged fermentation by filamentous fungi. The FPase quantitative assay was performed using 3.5 dinitroxalicylic acid on a microplate reader with absorbance at 540 nm. The specific activity of crude enzymatic preparations was also quantified. The filamentous fungi that formed light halos around the wells in the gel diffusion assay were submitted to the microculture for conventional identification of genera. Twenty-eight filamentous fungi were isolated. Among these, seven filamentous fungi potentially producers of cellulolytic enzymes, which belonged to the genus Aspergillus sp., Penicillium sp. and Curvalaria sp., were selected. EI ranged from 1.92 to 8.54. All filamentous fungi that presented EI greater than 1 (one) produced crude enzymatic preparation with total cellulolytic activity also evidenced in the qualitative gel diffusion assay. PFase values varied between 0.01299 filter paper units per mililiter (FPU.mL-1 (Penicillium sp. BM9 with 48 h of fermentation) and 0.05013 FPU.mL-1 (Aspergillus sp. CO2 with 72 h of fermentation) and the values of specific activity ranged from 0.04755 FPU.mg-1 of protein (Aspergillus sp. CO2 with 24 h fermentation) and 0.56407 FPU.mg-1 protein (BM18 with 72 h of fermentation). These results were promising when compared with the results of literature. There is potential for the obtainment of values of cellulolytic activity higher than the values found in the present study, so further studies of production optimization are required. Future studies investigating endoglucanases and β-glycosidases are needed to evaluate synergism because fungi produce different amounts of enzymes of the cellulolytic complex.